1994
DOI: 10.2466/pr0.1994.74.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Learning Processes and Academic Achievement of United Arab Emirates College Students

Abstract: The purpose of the present investigation was to examine the relationships between scores on the learning processes assessed by the Inventory of Learning Processes and academic achievement assessed by high school average (HSA) and grade point average (GPA) for 124 undergraduate college students. Multivariate analysis of variance indicated that students with high HSAs tended to score higher on Deep Processing and Fact Retention scales than students with low HSAs. Students with high GPAs appeared to score higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As predicted, in our sample, students who prioritized grades displayed a lower GPA than those who did not. Interestingly, Albaili (1994) found GPA to be positively related to students' active semantic processing. We found the opposite results (i.e., GPA declined with activities seen as relying on understanding), suggesting that habits, acquired in elementary and high school, might be difficult to discard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted, in our sample, students who prioritized grades displayed a lower GPA than those who did not. Interestingly, Albaili (1994) found GPA to be positively related to students' active semantic processing. We found the opposite results (i.e., GPA declined with activities seen as relying on understanding), suggesting that habits, acquired in elementary and high school, might be difficult to discard.…”
Section: Discussionmentioning
confidence: 99%
“…Besides local measures of course performance, it is of interest to determine the extent to which a comprehensive measure of students' performance, such as grade point average (GPA), is reflected in active learning items. If indeed active learning has a positive impact on students' achievement (Albaili, 1994; Ullah & Wilson, 2007), it is reasonable to expect that the greater is assessment's reliance on active learning in a variety of courses, the more survey items reflecting such learning will be positively correlated with GPA. Interestingly, it has been reported that students who have extensively practiced memorization and recitation of the Quran often exhibit greater academic achievement (Iqbal & Ahmad, 2015; Yusuf, 2010).…”
Section: Introduction and Rationalementioning
confidence: 99%
“…For instance, does practice with rote memorization (within the moderate range) reflect students' discipline and motivation toward academic activities that contribute to academic success? The extant literature offers a mixed answer to this question with findings of either a positive (Nield, 2004;Park, 2000;Zakaria, Ahmad, Awang, & Safar, 2021) or a negative relationship (Albaili, 1994;Keloyan, 2020;van Rossum & Schenk, 1984) between memorization (as a learning style) and students' achievement. Yet, in most studies, specific preferences for modes of learning rarely reveal the extent to which such modes are actually practiced.…”
Section: Memorizationmentioning
confidence: 99%